House of shadows - Coates, Darcy (Naperville, Illinois : Poisoned Pen Press, 2020)
"Sophie's world is shattered when disaster bankrupts her family. Marrying the mysterious Mr. Argenton may restore her family's fortunes and save them from scandal, but it condemns Sophie to a life in Northwood, a vast and unnaturally dark mansion situated hours from civilization. Still, she must do her duty. As time passes, Sophie struggles to adjust to her new position as mistress over the desolate house. Mr. Argenton's relatives are cold, and Mr. Argenton himself is keeping secrets. Even worse, the house is more than it seems..."--
"Originally self-published in 2016 by Black Owl Books."
Keywords: Ghost stories